The indexing of biography as a special genre or as historically documented text. (1st June 2021) - Sutcliffe, Glyn
Abstract : The indexing of biography as a genre, per se, is reconsidered with respect to subject indexing in general and the histories of lives in particular. The index of a biography of the chess player Bobby Fischer is compared with the index of a history of chess at the height of the Cold War conflict in which Bobby Fischer was the central protagonist. Some received theory of the indexing of biographies is critiqued and challenged by practical comparisons. Indexing from a literary perspective is considered and contrasted with back-of-book indexing from an information retrieval standpoint.